PENGARUH MOBILISASI DINI TERHADAP INVOLUSI UTERUS PADA IBU POSTPARTUM DI KLINIK PRATAMA YUSNIMAR PEKANBARU - Rini Hariani Ratih; Sara Herlina Herlina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
The puerperium begins after parturition is over, and ends after about 6 week Changes in these genetical organs in their entirety are called involution. Post partum post partum mothers experience uterine involution, where the muscles of the uterus contract so that blood vessels that are opened due to attachment of the placenta will be pinched, so that post partum hemorrhage can be prevented, uterine involution is influenced by three things namely autolysis, muscle activity and ischemia. Early mobilization is very important for postpartum mothers to accelerate the decline in the height of the fundus of the arteries. This study aims to determine the Effect of Early Mobilization on Uterine Involution in Post Partum Mothers in the Pratama Yusnimar Pekanbaru Clinic. The sample in this study was Post partum mothers, which fit the researchers' inclusion criteria. This study used a pre-experimental design with a One Group Pretest-Posttest design. The subject group was held pretest before being given treatment then measured by posttest after treatment. The results of the study using the Wilcoxon test with a significance level α ≤ 0.05 comparing the pre-test and post-test values obtained a significance level of P-Value = 0,000 which is smaller than α ≤ 0.05 means Ho is rejected. It can be concluded that there is an effect of early mobilization on uterine involution in post partum mothers in the Pratama Yusnimar Pekanbaru Clinic.